2020
DOI: 10.1042/bsr20193158
|View full text |Cite
|
Sign up to set email alerts
|

miR-154-3p and miR-487-3p synergistically modulate RHOA signaling in the carcinogenesis of thyroid cancer

Abstract: Correspondence: Ning An (anning gpch@tom.com) Background: miRs family members are often thought to have extensively overlapping targets and synergistically to modulate target gene expression via post-transcriptional repression. The present study was to determine whether miR-154-3p and miR-487-3p synergistically collaborated to regulate RHOA signaling in the carcinogenesis of thyroid cancer. Materials and methods: Candidate miRs were filtrated using miR microarray assays. Gene and protein expression levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Here, we first confirmed that circ_0008274 mediated SLC7A11 expression by sponging miR-154-3p. MiR-154-3p has been demonstrated to be involved in the pathogenesis of lung cancer, breast cancer and PTC [16,29,30]. Here, we first identified that SLC7A11 was a functional target of miR-154-3p in regulating PTC progression in vitro.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Here, we first confirmed that circ_0008274 mediated SLC7A11 expression by sponging miR-154-3p. MiR-154-3p has been demonstrated to be involved in the pathogenesis of lung cancer, breast cancer and PTC [16,29,30]. Here, we first identified that SLC7A11 was a functional target of miR-154-3p in regulating PTC progression in vitro.…”
Section: Discussionmentioning
confidence: 86%
“…Growing evidence has highlighted the association between miRNAs and PTC progression [14,15]. It was reported that miR-154-3p was down-regulated in thyroid cancer and correlated with the outcome of the disease [16]. The study also unraveled the involvement of miR-154-3p in thyroid cancer development through targeting ras homolog family member A (RHOA).…”
mentioning
confidence: 93%
“…However, we did not observe any significant changes in stat3 mRNA expression in the DRG in the context of arthritis, suggesting that STAT3 may not be a direct of target of miR-554-3p in the DRG under arthritis conditions. In cancer tissues, miR-544-3p functions as a tumor suppressor by directly targeting a variety of genes, such as ras homolog family member A (RHOA) and Toll-like receptor 2 (TLR2) 36,37,47 . Further investigation is required to explore whether any of these potential targets mediate analgesic effects of miR-544-3p in the setting of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that miR-544-3p downregulation contributes to the maintenance of arthritis pain, at least in part, through the regulation of FcγRI expression in the DRG. However, we cannot exclude the possibility that miR-544-3p regulates the expression of other genes [35][36][37] .…”
Section: Mir-544-3p Mimic Alleviates Arthritis Pain In the Mouse Cia Modelmentioning
confidence: 97%
“…Previous studies also pointed out that miRNAs regulated RhoA expression in multiple cancers [21,22] . For example, Fan et al demonstrated that miR-154-3p and miR-487-3p speci cally repressed RhoA expression at the post-transcriptional level in thyroid cancer [23] . Furthermore, miR-101 negatively regulated EMT and migration capacity of cancer cells by directly reducing the RhoA level [24] .…”
Section: Discussionmentioning
confidence: 99%